Professionalising teaching in HE: the impact of an institutional fellowship scheme in the UK. Issue 1 (2nd January 2018) - Shaw, Rob
ABSTRACT: The professionalisation of teaching in higher education has been increasingly prioritised across the globe in response to changes in the scale and nature of higher education brought about by massification, marketisation and managerialism. The UK experience has been characterised by the application of codified professional standards and this is of wider interest as perhaps the most developed attempt to formalise and systematise approaches to teacher development utilising such standards. Increasingly, this has focused on the ongoing development of existing staff in addition to new entrants to the profession. Institutional schemes underpinned by the United Kingdom Professional Standards Framework have rapidly spread throughout the sector offering a route for experienced staff to achieve fellowships of the UK Higher Education Academy. However, research into the effects of such schemes on individual participants and institutions has been limited. This article analyses the impact of such a scheme within the Faculty of Health and Social Sciences at Leeds Beckett University in the UK, drawing on data derived from in-depth interviews with scheme participants. Practice theories were applied as a frame for analysis of the developmental impact of the scheme through exploration of the practices involved in participation and how these meshed with other practices related to teaching and learning. This suggested that whilst such schemes may be an acceptable form of retrospective benchmarking, the ongoing developmental impact may be limited.